VIDEO ANIMASI MOTION GRAPHIC DAN TIPOGRAFI KINETIK SEBAGAI MEDIA SOSIALISASI PENCEGAHAN VIRUS CORONA - Krisbiantoro, Dwi; Handani, Sitaresmi Wahyu; Falah, Ilfa Jawahiril (Jurnal Bahasa Rupa, 2021)
Animation is a static image that is displayed sequentially so that the image becomes a moving image. Apart from being an entertainment, animation has also become a guide, an inspiration, as well as a means of socializing. Along with the development of technology, there are many techniques for making animation. These techniques aim to improve the quality of the image, as well as the animation movement itself. There is a lack of awareness to maintain health in society today. Many people do not understand the importance of maintaining health to stay healthy. Recently, there has been an unclear paradigm towards the transmission of the Covid -19 virus. The spread of a virus that is very mobile, will definitely have a bad impact. This is exacerbated by the state of unclear issues, where there is a lack of socialization of the preventive action of the Covid-19 virus, especially in Indonesia. Based on these things, in this study a socialization video was made about preventing the spread of the Covid -19 virus, based on 2-dimensional animation using kinetic typography techniques. So, the final result of this research is in the form of an animated video as a 2-dimensional based socialization media regarding the prevention of transmission of the Covid -19 virus to the public visually in the form of an animated video.